Mixed-litter effects of fresh leaf semi-decomposed litter and fine root on soil enzyme activity and microbial community in an evergreen broadleaf karst forest in southwest China - Mao, Bing; Cui, Tingting; Su, Tongqing; Xu, Qiangsheng; Lu, Feng; Su, Hongxin; Zhang, Jianbing; Xiao, Shuangshuang (Frontiers in Plant Science, 2022)
Litter decomposition is the main process that affects nutrient cycling and carbon budgets in mixed forests. However, knowledge of the response of the soil microbial processes to the mixed-litter decomposition of fresh leaf, semi-decomposed leaf and fine root is limited. Thus, a laboratory microcosm experiment was performed to explore the mixed-litter effects of fresh leaf, semi-decomposed leaf and fine root on the soil enzyme activity and microbial community in an evergreen broadleaf karst forest in Southwest China. Fresh leaf litter, semi-decomposed litter and fine root in the Parakmeria nitida and Dayaoshania cotinifolia forests, which are unique protective species and dominant species in the evergreen broadleaf forest, were decomposed alone and in all possible combinations, respectively. Our results showed that the mass loss of fresh leaf litter in three mixed-litter treatment was significantly higher than that in two mixed-litter treatment in the P. nitida and D. cotinifolia forests. Mass loss of fine root in the single litter treatment was significantly lower in the P. nitida forest and higher in the D. cotinifolia forest compared to that in the other litter treatments. There were insignificant differences in the activities of β-glucosidase (BG) and leucine aminopeptidase (LAP) between control and mixed-litter treatment in the P. nitida forest and between control and single litter treatment in the D. cotinifolia forest. The N-acetyl-β-D-glucosaminidase (NAG) activity was significantly increased by the single litter decomposition of fresh leaf and fine root and three mixed-litter decomposition in the P. nitida and D. cotinifolia forests. The activity of acid phospomonoesterase (AP) in the decomposition of fresh leaf litter was lower in the P. nitida forest and higher in the D. cotinifolia forest compared to that in control. The most dominant soil bacteria were Proteobacteria in the P. nitida forest and were Actinobacteria and Proteobacteria in the D. cotinifolia forest. Shannon, Chao1, ACE and PD indexes in the mixed-litter decomposition of fresh leaf and semi-decomposition litter were higher than that in control in P. nitida forest. There were insignificant differences in observed species and indexes of Chao1, ACE and PD between litter treatments in the D. cotinifolia forest. Richness of mixed-litter significantly affected mass loss, soil enzyme activity and microbial diversity in the P. nitida forest. Litter N concentration and the presence of fresh leaf litter were significantly correlated with the mass loss and soil enzyme activity in the P. nitida and D. cotinifolia forests. These results indicated that the presence of fresh leaf litter showed a non-negligible influence on mixed-litter decomposition and soil enzyme activity, which might be partly explained by litter initial quality in the P. nitida and D. cotinifolia forests.